Removal of a temporal lobe cavernous angioma to control epileptic seizures in a patient with tuberous sclerosis complex. Issue 6 (June 2020) - Sakakura, Kazuki; Fujimoto, Ayataka; Ichikawa, Naoki; Baba, Shimpei; Enoki, Hideo; Okanishi, Tohru
Abstract: Purpose: A patient with tuberous sclerosis complex (TSC) and a left temporal cavernous angioma (CA) presented with treatment-resistant epilepsy. We evaluated the patient to determine the best treatment option. Patient and methods: A 7-year-old boy with TSC exhibited weekly impaired awareness seizures and was diagnosed with TSC based on the modified Gomez's criteria. The presence of cortical tubers had been noted by his physicians. However, left temporal CA had not been diagnosed. He was referred to our facility for further treatment at the age of 33. Presurgical evaluation in our facility revealed the brain tubers and left temporal CA. Based on his seizure semiology, magnetic resonance imaging, scalp electroencephalogram, and long-term video monitoring, we determined his seizures were from the CA and not the TSC network. We then performed intraoperative-electrocorticography (ECoG). Results: Because the ECoG showed epileptiform discharges from the surrounding area of the CA but not from other areas, we removed the CA. He has been seizure-free for more than 10 years. Conclusion: The higher likelihood of TSC as well as greater familiarity with this disorder might lead physicians to overlook the possibility of CA. Abstract : Tuberous sclerosis complex; Cavernous angioma; Intraoperative electro-corticography; Concomitance; Neurology; Surgery; Pediatrics; Medical imaging; Diagnostics.